Influence of Tall Fescue Baseball Infield Mowing Height on Ground Ball Speed - J. Hoyle; Gage M. Knudson (Kansas Agricultural Experiment Station Research Reports, 2017)
Athletic field conditions have been shown to influence playability. Results of ball-roll speed studies can be used to predict success of infield hits. Field trials were conducted at Rocky Ford Turfgrass Research Center, Manhattan, KS, to determine the influence of tall fescue baseball infield mowing height on ground ball speed and batter on-base success. Mowing heights of 1, 2, and 3 inches resulted in 1.77, 2.08, and 1.88 s ground ball times, respectively.
Keywords: mowing height; infield; ground ball speed